2022
DOI: 10.3390/s22197680
|View full text |Cite
|
Sign up to set email alerts
|

Learning Assurance Analysis for Further Certification Process of Machine Learning Techniques: Case-Study Air Traffic Conflict Detection Predictor

Abstract: Designing and developing artificial intelligence (AI)-based systems that can be trusted justifiably is one of the main issues aviation must face in the coming years. European Union Aviation Safety Agency (EASA) has developed a user guide that could be potentially transformed as means of compliance for future AI-based regulation. Designers and developers must understand how the learning assurance process of any machine learning (ML) model impacts trust. ML is a narrow branch of AI that uses statistical models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The methodology for Machine Learning (ML) systems in air traffic control, specifically in a conflict detection tool, is evaluated in [10]. Results revealed that the methodology lacks time-dependent analysis, indicating that for certain systems, standard classification and regression metrics cannot be universally applied due to their variability over time.…”
Section: Ai In Air Traffic Managementmentioning
confidence: 99%
“…The methodology for Machine Learning (ML) systems in air traffic control, specifically in a conflict detection tool, is evaluated in [10]. Results revealed that the methodology lacks time-dependent analysis, indicating that for certain systems, standard classification and regression metrics cannot be universally applied due to their variability over time.…”
Section: Ai In Air Traffic Managementmentioning
confidence: 99%
“…A conflict prediction tool is presented in [14] which detect SMI between pairs of aircraft. This data-driven approach proposed in this study extracts aircraft trajectory data from the OpenSky Network which provides real world ADS-B flight trajectories.…”
Section: Detailed Literature Reviewmentioning
confidence: 99%